Testing the nonlinear equations for dental age evaluation in a population of eastern China. (February 2021) - Wang, Jian; Wang, Miaochen; Shen, Shihui; Guo, Ying; Fan, Linfeng; Ji, Fang; Tao, Jiang
Highlights: Introducing the current situation of the traditional Demirjian method for dental age estimation. Assessing the new nonlinear equations (Qingdao model)'s applicability and validity. Comparing the differences and potential factors of the two cities in Eastern China. Abstract: Objective: The study evaluated the validity of the nonlinear equations (Qingdao model) for dental age assessment in an eastern Chinese population. Materials and methods: We studied 1073 digital panoramic radiographs of children aged 11–16 years from a Chinese Han population. Dental ages (DAs) were calculated using the Demirjian and the new model methods. Statistical significance was set at p < 0.05. For each method, differences between the chronological age (CA) and dental age were analyzed by paired t-tests and mean absolute error (MAE). Results: The discrepancies between CA and DA determined by Qingdao model were 0.18 and 0.30 years for males and females, respectively. While using Demirjian method, these differences were and 0.46 and 0.30. The Qingdao model's MAEs between DA and CA were 1.23 and 0.90 years in males and females, respectively. As for the Demirjian method, MAEs were 1.43 and 0.86 years in males and females. Conclusions: This study showed that the new nonlinear equations were more accurate than the traditional Demirjian method. Especially, the new nonlinear Qingdao model is more competitive in 11–14-year male groups and 15–16-year female groups. We recommend a combined Qingdao model and Demirjian method may reasonably reflect the CAs among children in the eastern Chinese population.